An Ecological Approach to Understanding Assessment for Learning in Support of Student Writing Achievement - Cowie, Bronwen; Khoo, Elaine (Frontiers in Education, 2018)
In this paper, we report on a project conducted in a New Zealand primary school that aimed to enhance the writing achievement of primary school boys who were achieving just below the national standard for their age or level through the use of peer feedback and information and communication technologies (ICTs). The project involved a teacher collaborative inquiry approach where all seven teachers in the school and the school principal participated to achieve the project aim. We adopt an ecological approach as a lens to offer a holistic and comprehensive view of how peer assessment and use of ICTs can be facilitated to improve writing achievement. Data were collected through teacher interviews and written reflections of practice and student learning, teacher analysis of student work, team meeting notes, classroom observations, and student focus group interviews. Findings from the thematic analysis of textual data illustrate the potential of adopting an ecological approach to consider how teacher classroom practices are shaped by the school, community, and wider policy context. At the classroom level, our ecological analysis highlighted a productive synergy between commonplace writing pedagogy strategies and assessment for learning (AfL) practices as part of teacher orchestration of an ensemble of interdependent routines, tools, and activities. Diversity, redundancy, and local adaptations of resources to provide multiple pathways and opportunities—social and material and digital—emerged as important in fostering peer assessment and ICT use in support of writing achievement. Importantly, these practices were made explicit and taken up across the school and in the parent community because of whole staff involvement in the project. The wider policy context allowed for and supported teachers developing more effective pedagogy to impact student learning outcomes. We propose that an ecological orientation offers the field a productive insight into the contextual dynamics of AfL as classroom practice that is connected to the wider community and that has long-term value for developing student independence and learning outcomes.